“I can Just Get all the Bits That I Need”: Practitioners’ Use of Open-Access Sport Science Podcasts - Shaw, Matthew P.; McNamara, Scott W. T. (Frontiers in Education, 2021)
The aim of the current investigation was to explore practitioners’ attitudes towards and reasons for listening to open-access podcasts. It is well accepted within the literature that sport and exercise practitioners, such as coaches and sport scientists, perceive numerous barriers to access of scientific and academic research. Open-access podcasts may provide an alternative platform for developing esoteric knowledge. Nine sport and exercise practitioners (including gym owners, nutritionists, and sport coaches) participated in the investigation. A single-semi structured interview was conducted, and data were analyzed using a thematic network analysis approach. Three themes were constructed from the data - flexibility of podcast listening, convenience of podcast listening, practitioners’ need for authentic and novel information.